Importance IT Role of IT Self-Efficacy towards Actual Competency, IT Usage, and Productivity: A Case Study on University Students - Susanto, Tony Dwi; Assani, Saffana; Caroline Chan (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
Teaching how to use technology and encouraging students to improve their learning productivity by using technology are challenging. This study aims to investigate the important role of IT self-efficacy towards IT actual competency, actual usage of IT, and productivity in the case of university students to propose a teaching strategy that can improve students’ competency from “know-what” to “know-how” continued to real usage and productivity. It produces a model of the relationships between IT self-efficacy, IT actual competency, actual usage of information technology, and productivity. The relationships were quantitively measured using data from 89 students. The construct validity of the measurement model was examined using convergent and discriminant validity analysis. The hypothesized model was tested using structural equation modeling and bootstrap analysis. The findings suggest that IT self-efficacy does not directly impact actual usage and productivity. Still, it directly affects IT actual competency, leading to actual usage and productivity. In terms of novelty, this study examines a comprehensive relationship between 4 variables: IT self-efficacy, IT actual competency, IT usage, and Productivity, while the other existing studies just examined the relationships between 2 variables: IT self-efficacy and IT actual competency, IT self-efficacy and attitude towards IT usage, IT self-efficacy and IT Usage. For practical contributions, this study highlights the importance of improving students’ IT self-efficacy as an initial strategy to motivate students to use technology in their learning process which can lead to improved productivity.